2010
DOI: 10.1002/ejoc.200900867
|View full text |Cite
|
Sign up to set email alerts
|

Effective Oxidation of Secondary Amines to Nitrones with Alkyl Hydroperoxides Catalysed by (Trialkanolaminato)titanium(IV) Complexes

Abstract: The effective catalytic oxidation of secondary amines to nitrones with alkyl hydroperoxides as the primary oxidants is described. The titanium alkoxide catalysts are protected from the water co-product by the combined use of a tightly binding trialkanolamine ligand and molecular sieves. Nitrones can be obtained in high yields (up to 98%) under homogeneous, anhydrous conditions and even in the absence of solvent. The reactions are fast (2-7 h) and good selectivity and complete conversion can be achieved with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Alkyl hydroperoxides such as cumyl hydroperoxide (CHP) and t-butyl hydroperoxide can be used as terminal oxidants in combination with (triphenolatoamino)titanium(IV) complexes (method H). 48 For comparison of the various methods for the oxidations of 1,2,3,4-tetrahydroisoquinoline are summarized in Table 2.…”
Section: Oxidation Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkyl hydroperoxides such as cumyl hydroperoxide (CHP) and t-butyl hydroperoxide can be used as terminal oxidants in combination with (triphenolatoamino)titanium(IV) complexes (method H). 48 For comparison of the various methods for the oxidations of 1,2,3,4-tetrahydroisoquinoline are summarized in Table 2.…”
Section: Oxidation Reactionmentioning
confidence: 99%
“…Various catalysts such as SeO 2 (method C), MTO (methods D and E; eq 8), (trialkanolamino)­titanium­(IV) complexes (method F), and platinum­(II) complex (method G) have been used for the oxidation with hydrogen peroxide. Alkyl hydroperoxides such as cumyl hydroperoxide (CHP) and t -butyl hydroperoxide can be used as terminal oxidants in combination with (triphenolatoamino)­titanium­(IV) complexes (method H) . For comparison of the various methods for the oxidations of 1,2,3,4-tetrahydroisoquinoline are summarized in Table .…”
Section: Synthesis Of Nitronesmentioning
confidence: 99%
“…[ 110 ] Later in 2010 this protocol was used by the same group to prepare chiral and achiral trialkanolamines and their titanium complexes to use them in catalytic amines to nitrones oxidation. [ 111 ]…”
Section: Trialkylamines Synthesismentioning
confidence: 99%
“…[110] Later in 2010 this protocol was used by the same group to prepare chiral and achiral trialkanolamines and their titanium complexes to use them in catalytic amines to nitrones oxidation. [111] Such trialkanolamines were used not only as ligands but also as a precursor to the chiral phase-transfer catalysts. In 2003 Takabe and co-authors reported the preparation of a series of such chiral aminotriols with R=PhOCH 2 , Ph, Cy, iPr via reaction of the corresponding epoxides with NH 3 .…”
Section: Epoxide Ring-openingmentioning
confidence: 99%
“…In addition, several heterogeneous catalysts have also been used. 21 Alternatively, the reaction can be also carried out in the presence of alkyl hydroperoxides, 22 oxone, 23 dimethyldioxirane, 24 m -CPBA, 25 Davis oxaziridine, 26 or molecular oxygen 27 as oxidant.…”
mentioning
confidence: 99%